Cash conversion cycle sensitivity by moderating role of exchange rates volatility on firm’s financial performance - Hussain, Sarfraz; Ali Golam Hassan, Asan; Quddus, Abdul; Rafiq, Muhammad; Chien Nguyen, Van (Business: Theory and Practice, 2021)
The cycle of cash conversion relates to the time spread between the value of cash paid for purchases and the cash receipt from turnover. Using the State Bank of Pakistan data, this study introduces the direct and moderating role of the exchange rate, effective through the efficient execution of the cash conversion cycle between Pakistani 302 manufacturing companies from 1999–2015. Using the fixed effect as the static panel model and system GMM as a dynamic panel, it is observed that the exchange rate plays an authoritative moderating role between the cash conversion cycle and the financial performance. Results of the investigation have shown that in static panel analysis with the cash conversion period, the exchange rate has a positive and substantial moderating effect on return on assets and return on equity whereas that ER has a major negative impact on return on assets and return on equity using dynamic panel data analysis GMM. The issue of endogeneity in the static panel is addressed using the advanced approach of the standard error of the panel correction standard error method that changed the position of the significance of the moderator variable. Observers, therefore, intend to evaluate the fluctuations in the exchange rate as one of the variables of the financial output moderator in the context of current metrics such as asset’s returns, equity’s returns and gain more practical expression within their investigated results.